Mapping Transition Metal-Mn4 Macrocyclic Complex Catalysts Performance for the Critical Reactivity Descriptors - Zagal-Moya, J; Zagal-Moya, J (Elsevier B.V., 2021)
There has been a significant progress toward the development of highly active and stable platinum group metal-free (PGM-free) electrocatalysts for the oxygen reduction reaction (ORR) in polymer electrolyte fuel cells, promising a low-cost replacement for Pt group electrocatalysts. However, the success of such developments depends on the implementation of PGM-free electrocatalysts that are not only highly active but importantly, they also exhibit long-term durability under polymer electrolyte fuel cell operating conditions. This manuscript is an overview of the current status of a specific, most advanced class of PGM-free electrocatalysts: transition metal–nitrogen–carbon ORR catalysts. We present an overview for the understanding of catalysts’ performance descriptors for metal–nitrogen–carbon materials. © 2020 Elsevier B.V.